Progresivitas Perjanjian Daud - Andri Harvijanto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
God's covenant with David is a core part of understanding God's plan for the development of the realization of the restoration of the state of Israel in the midst of the nation's deterioration. David became an ideal figure for kings in the eschatological period. In the future the promise will be fulfilled, renewed and expanded. Through the prophet Nathan a promise was given to David (2 Samuel 7: 12-17). Furthermore, the continuation of the David covenant can be understood through God's plan for the development of the realization of the restoration of the state of Israel in the midst of the nation's deterioration. David became an ideal figure for kings in the eschatological period. Abstrak Indonesia Perjanjian Allah dengan Daud merupakan bagian inti untuk memahami rencana Allah bagi perkembangan perwujudan pemulihan keadaan Israel di tengah-tengah keterpurukan bangsa. Daud menjadi figur yang ideal bagi raja di masa eskatologis..Di masa yang akan datang janji itu dipenuhi, diperbaharui dan diperluas. Melalui nabi Natan janji diberikan kepada Daud (2 Samuel 7:12-17). Selanjutnya kesinambungan perjanjian Daud dapat dipahami melalui rencana Allah bagi perkembangan perwujudan pemulihan keadaan Israel di tengah-tengah keterpurukan bangsa. Daud menjadi figur yang ideal bagi raja di masa eskatologis.